2005
DOI: 10.3758/bf03193646
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of return for faces

Abstract: Inhibition of return (IOR) refers to slower reaction times when a target appears unpredictably in the same location as a preceding cue, rather than in a different location. In the present study, frontal images of human faces were presented intact as face configurations, were rearranged to produce scrambled-face configurations, or were pixilated and randomized to produce nonface configurations. In an orienting paradigm designed to elicit IOR, face and scrambled-face stimuli were used as cues (Experiment 1), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
26
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 21 publications
6
26
3
Order By: Relevance
“…It is unlikely that the similarity is due to a tendency for control participants to try to commit the task-irrelevant word cues to memory: A very similar, 10-ms, IOR effect was obtained by Taylor and Therrien (2005) in a task that presented face stimuli as cues in a target localization task (cue-target SOA = 1,000 ms). As with word cues, face stimuli are inherently meaningful; however, the same face stimulus was used trial to trial, and there would have been no reason for participants to commit the item to memory.…”
Section: Discussionmentioning
confidence: 83%
“…It is unlikely that the similarity is due to a tendency for control participants to try to commit the task-irrelevant word cues to memory: A very similar, 10-ms, IOR effect was obtained by Taylor and Therrien (2005) in a task that presented face stimuli as cues in a target localization task (cue-target SOA = 1,000 ms). As with word cues, face stimuli are inherently meaningful; however, the same face stimulus was used trial to trial, and there would have been no reason for participants to commit the item to memory.…”
Section: Discussionmentioning
confidence: 83%
“…Taylor and Therrien (2005) compared the magnitude of IOR (as expressed by manual motor responses) in response to neutral or scrambled face cues in a spatial cuing paradigm, but found no evidence that cue content influenced IOR. Stoyanova et al (2007) similarly found no difference in IOR magnitude in response to fearful, neutral, or scrambled face cues.…”
mentioning
confidence: 99%
“…Recently, IOR has emerged as a useful phenomenon to explore influence of peripheral cue content on exogenous control of covert attention (e.g., Fox, Russo, & Dutton, 2002;Stoyanova, Pratt, & Anderson, 2007;Taylor & Therrien, 2005;Theeuwes & Van der Stigchel, 2006). First discovered and investigated by Posner and Cohen (1984; see Klein, 2000, for a review), IOR refers to the finding that, after attention has been exogenously cued and then withdrawn from a location, attention is biased against returning to the region, indicated by inhibited processing of stimuli at (or near) the previously attended location relative to previously unattended locations.…”
mentioning
confidence: 99%
“…This would lead to a greater IOR response elicited by faces compared to other stimuli. Some of these studies have found an IOR effect for faces compared to other stimuli (Taylor & Therrien, 2008;Theeuwes & Van der Stigchel, 2006), while others have found no difference in IOR magnitude (Taylor & Therrien, 2005). However, it should be noted that these studies used a relatively narrow range of SOAs (e.g., 800-1,000 ms), so it is unknown what time course IOR may follow for face stimuli.…”
Section: Introductionmentioning
confidence: 89%
“…Sometimes, these studies use other control stimulus cues (e.g., household objects or scrambled faces) to compare the IOR response to faces (e.g., Taylor & Therrien, 2005;Taylor & Therrien, 2008;Theeuwes & Van der Stigchel, 2006;Weaver et al, 2012). In these paradigms, both types of stimuli should capture attention and lead to an IOR response.…”
Section: Introductionmentioning
confidence: 99%